Role of Redox Homeostasis in Recovery from Cryopreservation in Arabidopsis thaliana - Lukić, Milana (Curtin University, 2024)
Oxidative stress is a major barrier to the success of cryopreservation as a conservation method, having been associated with poor cryopreservation results in multiple plant species. This thesis found that antioxidants play an essential role in post-cryopreservation regeneration. It used studies of DNA stability as well as transcriptomic changes to examine responses of plant model species Arabidopsis thaliana to cryopreservation process.